Stimulation by fenfluramine of glucose uptake into skeletal muscle in vitro. - Frayn, K; Hedges, A; Kirby, M (1974)
The weight reducing agent fenfluramine hydrochloride (100 ng/ml) was found to stimulate by 43% the glucose uptake by the rat isolated hemidiaphragm without increased glycogen deposition.